2015
DOI: 10.1089/end.2015.0358
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Magnetic Resonance Imaging on Prediction of Extraprostatic Extension and Prostatectomy Outcome in Patients with Low-, Intermediate- and High-Risk Prostate Cancer: Try to Find a Standard

Abstract: Prediction of pT(3) disease is crucial to plan NSS and to achieve negative SM in RP. Standardized ECE scoring on mpMRI is an independent predictor of pT(3) and may help to plan RP with oncologic security, even in high-risk patients. In addition, it allows more accurate selection of a subgroup of patients for systematic and MRI-guided IFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 31 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Retrospective review showed 25.7% of men who had no evidence of ECE on mpMRI and who underwent a non-nerve-sparing procedure due to high-risk features, ultimately had OC disease at final pathology. Conversely, mpMRI was able to predict pathologic ECE in low or intermediate risk patients in patients who underwent nerve-sparing procedures and subsequently had a positive surgical margin [35] .…”
Section: Discussionmentioning
confidence: 91%
“…Retrospective review showed 25.7% of men who had no evidence of ECE on mpMRI and who underwent a non-nerve-sparing procedure due to high-risk features, ultimately had OC disease at final pathology. Conversely, mpMRI was able to predict pathologic ECE in low or intermediate risk patients in patients who underwent nerve-sparing procedures and subsequently had a positive surgical margin [35] .…”
Section: Discussionmentioning
confidence: 91%
“…Our analyses showed that for 5 studies using the PI-RADS guidelines to diagnosis of PCa, the diagnostic accuracy was lower than quantitative assessment. Moreover, sensitivity and specificity varied widely as whether PI-RADS score 3 lesions were regarded as positive or not, and many studies demonstrated that counted score 3 lesions as positive would result in higher sensitivity but lower specificity, and vice versa 2,25,38. Another widely used scoring system was Likert scale, and a study conducted by Costa et al showed that it perhaps outperforms PI-RADS but the difference was not substantial; moreover, the absence of objective criteria raises the concerns about the reproducibility of it, and then a strategy to standardize the Likert scoring system would be desirable 33.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this issue, better preoperative patient selection is mandatory, not only for hydrodissection but also for the indication of nervesparing procedure. Recent publications showed the impact of multiparametric magnetic resonance imaging (MRI) on prediction of extraprostatic extension with a positive predictive value of 50.0%, 90.0%, and 88.8% for the low‐, intermediate‐ and high‐risk cohort . Other authors report an overall sensivity of 60.0% and specifity of 86.0% and therefore suggest preoperative MRI to guide decision‐making about NVB preservation .…”
Section: Discussionmentioning
confidence: 99%